SIRT4 and SIRT6 Serve as Novel Prognostic Biomarkers With Competitive Functions in Serous Ovarian Cancer - Wang, Huihuan; Li, Juan; Huang, Rui; Fang, Lei; Yu, Shan (Frontiers in Genetics, 2021)
Sirtuins (SIRTs) are known as class III HDACs, including seven members widely expressed in mammals. Accumulating evidence show that Sirtuins may have contradictory roles in malignancies. They majorly participate in metabolic homeostasis, DNA damage repair, cell survival and differentiation as well as other cancer-related biological processes. To deeply understand their prognostic role and biological functions, we used comprehensive bioinformatics analysis to demonstrate the expression and mutation of Sirtuins family in ovarian cancer with their value in prognostic prediction including anti-ovarian cancer drugs. Moreover, co-expression genes of Sirt4 and Sirt6 with contradictory survival prediction value in both overall and progression-free survival time were further analyzed through Gene Ontology enrichment and Kyoto Encyclopedia annotation. In addition, we obtained the IHC staining pattern of those two biomarkers from the serous ovarian cancer patient database to display the potential clinical practice in pathology. According to our findings, Sirt4 and Sirt6 were new prognostic biomarkers, which may serve as contradictory competitor for ovarian cancer cell survival. They are also sensitive biomarkers for the prediction of Avastin’s anti-cancer effect. As Sirt4 is related to the immune response during oocyte maturation, Sirt6 also participates in immune-related disease pathways and mitochondrial metabolism mediated DNA translation. Those findings contributed to a novel hypothesis that Sirt4 and Sirt6 are acting as contradictory competitors in regulating ovarian cancer behavior. More further studies are required to validate our notion.